THE RESISTANCE AGAINST ARISTOCRACY IN FRANCE REVOLUTION AS SEEN IN CHARLES DICKENS A TALE OF TWO CITIES - Dai, Kevin; Samola, Nurmin F.; Rorintulus, Olga (SoCul: International Journal of Research in Social Cultural Issues, 2022)
The purpose of this study is to reveal the causes of resistance against Aristocracy in France Revolution as seen in Charles Dickens A Tale of Two Cities < em> This research employs a qualitative method which is richly descriptive In conducting this research the data was taken from primary which is Dickens A Tale of Two Cities < em> and secondary sources The historical approach to literature simply means that the critic the person trying to understand any work of literature looks beyond the literature itself to the broader historical The findings show that the resistance against aristocracy arises as a result of conditions in poverty that still dominate most of the community in which the community received improper treatment The government services to the community in Charles Dickens A Tale of Two Cities< em> were considered a failure and were made worse by the dirty and slum environmental conditions of the community which made the people angry and human rights violations also occurred The author views that the study s conclusions would encourage readers to evaluate literary works and comprehend the historical events the novel portrays < p>